PERANAN SISTEM INFORMASI AKUNTANSI DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA UD NANITA - Windiati, Aulia Desy; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to analyze the role of accounting information systems in raw material inventory control, in the form of activities and procedures which is related to the accounting information system, raw material inventory control system and sales targets at UD Nanita. This research uses descriptive and qualitative methods. The steps which has been taken to achieve the objectives of this research are: descriptive analysis of the accounting information system of raw material supply and internal control which has been applied by the company by identifying problems and causes of the problems which has been encountered by the company, calculating analysis of sales targets that can be achieved by the company. The result of the research shows that UD Nanita has inventory information system and internal control that support the business, but the inventory accounting information system and internal control of companies is still required to be improved and supervised, The issues which occurrs in the UD Nanita is the mismatch between the total amount of inventory on the card stock and the execution of tasks on each department which is still not in accordance with the actual tasks, then the calculation of the sales target is determined based on the reports from previous sales.Keywords: Inventory accounting information system, internal control, stock card, sales target.